Adults with achondroplasia exhibit a high probability of specific micronutrient inadequacy and low physical activity levels: a cross-sectional study - Inês Alves; Maria António Castro; Sofia Tavares; Orlando Fernandes; Cidália D. Pereira (Journal of Rare Diseases)
Abstract Purpose Achondroplasia is a rare skeletal dysplasia, characterized by disproportionate short stature and predisposition to obesity. There is limited evidence on nutritional adequacy in adults with achondroplasia. This study aimed to assess nutrient intake and adequacy in adults with achondroplasia, exploring associations with anthropometric characteristics and physical activity patterns. Methods An exploratory cross-sectional study evaluated 16 Portuguese adults with achondroplasia (10 women), aged 38.4 ± 13.8 years). Nutrient intake was assessed using a validated food frequency questionnaire and evaluated against reference values from the European Food Safety Authority. Anthropometric body composition parameters were assessed using standardized methods and physical activity levels using the International Physical Activity Questionnaire. Results Most participants (62.5%) exhibited high body mass index (≥ 30 kg/m2), with 43.8% presenting waist-to-hip ratio above WHO cut-offs and elevated fat mass percentage (27.0 ± 10.5). Macronutrient distribution largely aligned with recommendations, yet 43.8% exceeded saturated fat intake while 100% presented lower intakes of omega-3 fatty acids and 57.3% lower fiber intake. High probability of inadequacy was found for vitamin D, vitamin K, biotin, manganese, and molybdenum. Pantothenic acid, vitamin E, and iodine intakes were also concerning. Sodium intake exceeded recommendation in 75% of participants. Physical activity levels were low, with 56.3% of participants categorized as inactive. Conclusions This study provides novel insights into nutritional inadequacies and sedentary lifestyle in adults with achondroplasia, highlighting the need for tailored dietary interventions and adapted physical activity programs. Promotion of the Mediterranean dietary patterns may also offer benefits for nutritional adequacy in this population.